Quantitative Evaluation of the Shape of Graphite (Circularity) in Graphitic Cast Irons - Vasko, Alan; Belan, Juraj; Uhricik, Milan; Zatkalikova, Viera (Manufacturing Technology Journal, 2017)
Shape of graphite in graphitic cast irons is the most important microstructural parameter affecting mechanical properties. The paper deals with evaluation of the shape of graphite in cast irons by shape factor (circularity). Three specimens of graphitic cast irons with different shape of graphite (lamellar, vermicular and nodular) were used for experiments. The aim of this study has been to understand the influence of microstructure (especially shape of graphitic particles) on mechanical properties of graphitic cast irons. However, the evaluation of shape factor is a subject of interest in many fields of applications such as medicine and industrial processes, not only materials engineering. The shape factor plays an important role in materials science as a way to understand the relationship between microstructure and mechanical properties of technical materials.
Keywords: Cast iron; Graphite; Shape factor; Circularity; Nodularity